2008
DOI: 10.1002/eji.200737905
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG‐infected neutrophils and dendritic cells cooperate to induce specific T cell responses in humans and mice

Abstract: Neutrophils are increasingly thought to modulate dendritic cell (DC) functions. We investigated the role of the neutrophil-DC partnership in the response to Mycobacterium bovis BCG-the vaccine used against tuberculosis. We compared neutrophil-DC crosstalk in humans and mice, searching for functional differences. In both species, neutrophils captured fluorescent BCG-enhanced green fluorescent protein (EGFP) and were more phagocytic than DC. Non-apoptotic BCG-infected neutrophils clustered with immature DC, esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 49 publications
3
72
1
Order By: Relevance
“…3A). Mouse neutrophils produce TNF in response to BCG infection (13). Similar levels of intracellular TNF staining were observed for neutrophils and CD11b + Ly-6C int Ly-6G 2 cells after BCG infection (Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…3A). Mouse neutrophils produce TNF in response to BCG infection (13). Similar levels of intracellular TNF staining were observed for neutrophils and CD11b + Ly-6C int Ly-6G 2 cells after BCG infection (Fig.…”
Section: Resultssupporting
confidence: 74%
“…Notably, understanding inflammatory/innate response to the tuberculosis vaccine Mycobacterium bovis bacillus Calmette-Guérin (BCG) might give some clues as to why BCG does not consistently protect adults against pulmonary disease (11). We showed that during BCG vaccination in mouse models, neutrophils shuttle BCG from the skin to the draining lymph node (12) and establish cross-talk with DCs to facilitate the presentation of Ag to T cells (13).…”
mentioning
confidence: 99%
“…Neutrophils are acute inflammatory cells that respond to mycobacterial infection. They engulf bacilli efficiently, both in vitro and in vivo (12,13). They also play a key role in granuloma formation through the secretion of CXCR3 ligands that recruit CD4 T cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are highly efficient phagocytic cells (12) and also play an important role during mycobacterial infection. In an intradermal BCG vaccination model in the mouse, we demonstrated that neutrophils recruited to the injection site could transfer live bacilli to the draining lymph node (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation